Fabrication and Characterization Fe3O4/Humic Acid for the Efficient Removal of Malachite Green - Nur Ahmad; Zaqiya Artha Zahara; Alfan Wijaya; Fitri Suryani Arsyad; Idha Royani; Aldes Lesbani (Science and Technology Indonesia, 2023)
The dye pollutants that contaminate water and food resulting from commercial manufacture and illicit addiction are a worldwide threat that harms the ecosystem, the food supply, and the health of humans. Magnetite/Fe3O4 humic acid (MHA) with various ratios was synthesized using a two-step process involving coprecipitation and hydrothermal treatment in order to effectively overcome these obstacles. Analyses of SEM, XRD, FTIR, and VSM were used to describe the morphology and physicochemical aspects of MHA. The adsorption kinetics studies indicated that the adsorption mechanism of malachite green adhered to the pseudo-second-model and that the adsorption was adequately described by the Langmuir isotherm. The thermodynamic studies demonstrated spontaneous, endothermic, disorderly adsorption. MHA2 had maximal malachite green adsorption capacities of 83.333 mg/g. Malachite green and MHA may interact via interaction, electrostatic attraction, van der Waals forces, H-bonding, pore filling, pore locking, and/or mechanical adhesion; however, physisorption dominates the adsorption process. Malachite green's adsorption characteristics change significantly after up to four cycles. It has been demonstrated that MHA has a high capacity for dye adsorption and a broad range of potential applications.